Preliminary biological data of Sahel wetland ecosystems in Burkina Faso: Implications for ecological health assessment - Kaboré, Idrissa; Tampo, Lallébila; Bancé, Victor; Daboné, Clément; Mano, Komandan; Ayoro, Halamoussa Joëlle; Ouéda, Adama (Frontiers in Conservation Science, 2022)
Birds, amphibians, fish, and macroinvertebrates are useful indicators of ecological conditions and ensure considerable conservation value and tools for decision making in management of wetland ecosystems. However, the use of these organisms to monitor wetland ecosystems has rarely been explored in Western Africa. Whereas, we are currently facing to growing multiple anthropogenic pressures and climate warming that impact negatively our wetlands and the biodiversity. Notably, there is an urgent need of cost-effective tools for wetland ecosystems health assessment in Burkina Faso. In this study, we examined the taxonomic composition of birds, amphibians, fish, and macroinvertebrates and explored their potential use for monitoring wetland ecosystems. From our findings, measures of taxa composition and diversity respond to the gradients of anthropogenic alterations. Our results revealed that the highest diversity of fish and macroinvertebrates taxa was recorded in protected sites, whereas the lowest diversity was obtained in degraded sites. Additionally, the findings showed a strong and positive correlation between macroinvertebrates taxa and key water variables, whereas fish taxa were strongly correlated to xylal (deadwood) substrates. Most of bird’s species were recorded in tree-shrubs, and amphibians of protected wetlands were distinguished by identifying indicator taxa through indicator value index. African wetland ecosystems and biodiversity may be sustainably preserved through responsive monitoring programs of wetlands by limnologists.